String music of the baroque era for string quatet or string orchestra Viola - CLARKE, Irma (The Boston Music, 1911)
Menuetto..CorellinGavotte...RameaunIa rejouissance...HandelnBadinerie..J.S. BachnHornpipe and air......Purcel